Pondok Pesantren sebagai Pusat Otoritas Ulama Madura - Hasanatul Jannah (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2019)
This study examines and recognizes that Madurese ulama (Islamic Scholars) are represented as charismatic characters placed in a strategic social layer who are influential to their society. Therefore, they have high authority in religious, social and cultural aspects. The manifestation of their scholarly traist are usually displayed in signs of their devotion in practicing religion, consistency in practicing their knowledge, being a role model and having the ability to transform knowledge in the midst of their society. The figure of a scholar in Madura is inseparable from his ownership of Islamic boarding schools (Pesantren) where they become the main center of the scholars’ work on social and religious authority. This study discovered that Madurese scholars established and developed their authority in Islamic boarding schools; making it hard for the world of Islamic boarding schools to be separated from the lives of Madurese scholars. Therefore, the Islamic boarding school became the main authority center. The Islamic Boarding Schools’ path is psychologically related to being more attached and they tend to generate significant mass. The emotional attachment between the santri (students of Islam) and their ulama (Islamic Scholars) will strengthen the authority of the scholars in all aspects of life.